Immigration Policy and Less-Skilled Workers in the United States: Reflections on Future Directions for Reform - Harry J. Holzer (Institute for the Study of Labor (IZA), 2011)
This paper reviews the evidence on the effects of less-skilled immigration to the U.S., and their implications for immigration reform. It begins with a review of the costs of less-skilled immigration, in terms of competition to native-born American workers; and the benefits of such immigration in the form of lower consumer prices, higher employer profits, and greater efficiency for the U.S. economy. Effects of different legal categories of immigrants and of immigrant integration over time are considered. The paper then reviews various reform proposals and other ideas that might raise the net benefits associated with less-skilled immigration to the U.S.
Keywords: J1; J15; J18; 330; immigration; employment; less-educated workers; Einwanderung; Ungelernte Arbeitskräfte; Migrationspolitik; Reform; USA